PSYCHOANALYSIS FACING CONTEMPORARY HUMAN SUBJECTIVITY - Mara Geronutti , Priscila (Health and Society, 2021)
The article brings an analysis of the contemporary human subjectivity with the psychoanalysis of Sigmund Schlomo Freud. Within the psyche of every human being, where the unconscious keeps memories, desires, pleasures, anguishes, repressions, often incontestable, causes the subject to relate them to pain, as something to be avoided. Today, in the face of contemporaneity, one observes that subjectivity is intertwined with the fear of discovering itself, with the fear of facing its own history and reality, seeking only to live momentarily, to live the present, to live the uncreated, without perspectives. In this context it is observed that the figure of Freud, or rather, the emblematic psychoanalysis, gains space more and more for his rescue, from when it was postulated. The search for happiness that most people believe to exist is implicitly linked to the action and attitude of every human being, since we know ourselves as such, independent of concrete subjective worlds or not. Therefore, the place of psychoanalysis, in the face of this context, is understood as a contraposition to the avoidance of pain, characteristic of the pursuit of present happiness.